Fly away Peter - Morgan, Stevie (Hodder & Stoughton, 1999)
Even though it is five years since Peter died, Myfanwy still has memories constantly playing in her head. Her only social contact is with her cousin and his family. Until the arrival of David, he too is stuck in the past and together they let go.